HPA-axis activity and the moderating effect of self-esteem in the context of intimate partner violence in Cameroon. Issue 1 (1st January 2021) - Wadji, Dany Laure; Gaillard, Claudie; Ketcha Wanda, Germain Jean Magloire; Wicky, Chantal; Morina, Naser; Martin-Soelch, Chantal
ABSTRACT: Background: The experience of intimate partner violence (IPV) is stressful. One objective way to monitor it is to assess victims' stress response by measuring the concentration of their salivary cortisol, the major stress hormone released by the hypothalamic–pituitary–adrenal axis. Objective: We investigated how the IPV experienced by women in Cameroon affects their stress levels and those of their children. Method: We recruited 50 mother–child dyads exposed to IPV and a control group of 25 mother–child dyads. All mothers completed questionnaires, including the Revised Conflict Tactics Scale to assess IPV, the Sense of Coherence Scale, and the Self-Esteem Scale, to assess their psychological resources. Mothers were asked to collect 3 saliva samples from themselves and 3 from their children on a single weekday: immediately after waking up, 30 minutes after waking up, and 45 minutes after waking up. The total cortisol secretion over the first hour after awakening was determined by calculating the area under the curve with respect to the ground (AUCg). Results: Mothers exposed to IPV exhibited higher total post-awakening cortisol concentrations compared with those in the control group. However, no significant difference was found between exposed and non-exposed children. In addition, higher IPV, specifically injuries, was significantly and positively associated with greater AUCg among mothers exhibiting lower self-esteem. When self-esteem was high, however, no significant effect of IPV on AUCg was observed. Conclusions: Of particular clinical significance is that self-esteem can modulate the stress levels of women exposed to IPV, a valuable insight into the development of effective psychosocial interventions to support IPV victims in sub-Saharan Africa. HIGHLIGHTS: Victims of intimate partner violence (IPV) experience extreme stress through elevated cortisol levels. Our results showed that higher cortisol levels was associated with lower self-esteem and a lower sense of coherence, thus implying that self-esteem may serve as a moderator.